Cryogenian magmatism along the north-western margin of Laurentia: Plume or rift? - Cox, Grant; Halverson, Galen; Denyszyn, S.; Foden, J.; Macdonald, F. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Here we present a new U-Pb baddeleyite ID-TIMS age of 713.7±0.9Ma on the shoshonitic Tatonduk Suite near the Yukon-Alaska border in the Proterozoic Tatonduk inlier, which occur as mafic and intermediate dykes and a sequence of basaltic to andesitic volcanic flows immediately beneath iron formation-bearing Sturtian glacial deposits correlated with the early Cryogenian Rapitan Group.Considering the age overlap with what is inferred to represent the Franklin Large Igneous Province (LIP) of northern Canada, the Tatonduk Suite might logically be considered a far-flung component of the Franklin Large Igneous Province. However, the Tatonduk Suite was emplaced in an actively extending environment >1200km from the plume head on Melville Island and does not obviously align with the Franklin dyke trend. Furthermore, major, trace and isotopic data on the Tatonduk Suite reveal a composition that is unique from the Franklin LIP and most likely reflects melting of potassic and trace element enriched sub-continental lithospheric mantle at pressures of less than 10kb. These volcanics and dykes highlight the complexity in defining what constitutes a LIP. The Tatonduk Suite either represent a non-plume end-member composition of the Franklin LIP, or more likely, rift volcanics associated with extension along the actively extending margin of northwestern Laurentia. Although the plume and rifting may be geodynamically linked, this interpretation suggests that this new age for the Tatonduk Suite does not constrain the timing of Franklin magmatism.The Tatonduk Suite was emplaced during the Sturtian Snowball Earth event and contributes to the growing body of geochronological data that indicates the onset of glaciation at ca. 717Ma. Furthermore, this age provides direct evidence for the syn-glacial origin of Sturtian iron formation in the Tatonduk inlier and further links iron formation to widespread mafic magmatism at this time.